Sudi Pendahuluan Pengaruh Karakteristik Batubara Peringkat Rendah Cekungan Kutai Terhadap Gasifikasi Batubara - Agus Winarno; D. Hendra Amijaya; Agung Harijoko (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2016)
The utilization of low rank coal (lignite and sub-bituminous) especially gasification is part of thedevelopment of coal conversion in Indonesia as drivers of the increase in value-added coal.Gasification is a process of change in the solid fuel into gas. In contrast to combustion, gasificationprocess is the process of breaking the carbon chains to form other chemical elements or compounds.This research was conducted by looking at the effect of the type of maceral, mineral and geochemicallow rank coal in the Kutai Basin. It also saw the effect of operating conditions (time and temperature),the condition of pyrolysis and gasification catalyst, so it will know the volume of the gas content of CH4,CO, CO2 and H2 results of the low rank coal gasification.